Is the negotiation of professional meanings possible in training? Theoretical proposals and illustrations - Escalié, Guillaume; Charliès, Sébastien (Swiss Journal of Educational Research, 2018)
The main proposals to fit out the teachers’ professional training programs in order to strengthen the university – school(s) partnerships are based on the theory of communities of practice (Lave & Wenger, 1991). Within this theory, these programs are considered as open training environments in which the meanings of ongoing professional experiences result from a negotiation process. Yet, the circumstances in which takes place this negotiation remain rather dark. This article aims at illustrating empirically theoretical postulates stemming from a theory of learning (Nelson, 2008) and collective action (Wittgenstein, 1996) to re-qualify the negotiation in professional training.